Cameroon : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The paper provides an overview of recent economic and social developments in Cameroon. The state and the dynamics of poverty has been analyzed. The pillars of the short- and medium-term growth and poverty reduction strategy have been described. The paper provides a quantitative assessment and costing of Cameroon's poverty reduction strategy, a consistency check between the macroeconomic framework and sector strategies, and estimates of the total cost of the strategy. It also explains how the poverty reduction strategy will be monitored and evaluated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet